Socio-cultural Causes of Gender Disparity in Nepalese Society - Shrestha, Anita; Gartoulla, Ritu Prasad (Journal of Advanced Academic Research, 2017)
Gender is socially constructed idea and disparity is the problem created by the society. The study was conducted from the socio-cultural perspective so the main objective of this study was to identify the socio-cultural causes of gender disparity in five different ethnic groups: Newar, Magar, Tamang, Rai/Limbu and Brahmin/Chhetri of Kathmandu Valley. Total 390 respondents were selected randomly from the all ethnic groups. Except the role of religion, the role of culture, patriarchy system, social perception, sources of income, level of education, political awareness & involvement and gender based division of labor had significant effect to increase the gender disparity in society. Political announcement that Nepal as a secular country had effected in the perception and practices related to the religious activities of people also. The government should address the socio-cultural problem and further researcher should explore the strategies to address the problem of gender disparity.